Water renewal in semi-enclosed basins: A high resolution Lagrangian approach with application to the Bay of Algeciras, Strait of Gibraltar - Sammartino, Simone; Sánchez-Garrido, José Carlos; Naranjo-Rosa, Cristina Belén; García-Lafuente, Jesús; Rodríguez-Rubio, Pablo; García-Sotillo, Marcos (Wiley Periodicals, Inc., 2018)
Lagrangian experiments of particle tracking were carried out in the semi-enclosed Bay of Algeciras attached to the Strait of Gibraltar in order to investigate the flushing patterns. A high resolution three-domain-nested hydrodynamic model provided the velocity fields from a 61-d hindcast, with the aim of analyzing the flushing efficiency of eight different docks under a variety of external conditions, namely, tide phase and strength, and winds. The tracking algorithm was specifically developed to exploit the high spatial resolution of the model that reproduces the local dynamics accurately. Winds are the dominant agent, with westerlies featuring e-folding times one order of magnitude lower than easterlies. Fortnightly tidal modulation causes a counter-intuitive effect, with spring tides promoting higher accumulation of particles inside the docks and higher e-folding times than neap tides. Additionally to high resolution details on the flushing patterns of the Algeciras Port, the model also confirms the Bay as a potential feeder of floating tracers for the nearby Alboran Sea. The proposed approach is easily scalable and exportable to other similar locations worldwide.
Keywords: Algeciras (Bahía, Cádiz); Bay of Algeciras; Water quality; Ocean modeling; Tidal currents